Clinical outcomes of closed, displaced phalangeal neck fractures in children with different types of kirschner wire fixation: A retrospective observational study - Wu, Chunxing; Song, Jun; Ning, Bo; Mo, Yueqiang; Wang, Dahui (Frontiers in Pediatrics, 2023)
Objectives Inappropriate treatment of Closed displaced phalangeal neck fractures (CDPNF) in children usually leads to poor outcomes.This study was to evaluate the clinical outcomes of closed/open reduction, age, and different types of fracture and Kirschner wire (K-wire) fixation in the treatment of CDPNF. Materials and methods Participants: Sixty patients (male, 46 and female,14; right-handed, 35 and left-handed, 25; mean age, 7.9-years-old [range, 1.0–14.5 years]) who had CDPNF were included. Preoperative x-rays showed that the fractures were displaced and exhibited obvious deformities. Interventions: First, reduction (four cases of open reduction and 56 cases of closed reduction) was performed followed by percutaneous K-wire fixation (cross fixation, 24 cases; longitudinal and slanting fixation, 17 cases; homolateral fixation, four cases; and single longitudinal fixation, 15 cases,) and immobilized by cast. x-ray examination following removal of the K-wires showed that the fractures were healed; the criteria for fracture healing were callus formation and the absence of fracture lines. Clinical outcome and radiographs between groups were compared. Results According to the visual analogue scale, the pain scores were excellent. According to the Al-Qattan Grade system(AGS),all the patients presented with closed, type II phalangeal neck fractures,the results were excellent in 36 cases (36/60, 60%), good in 15 cases (15/60, 25%), fair in 5 cases (5/60, 8.3%) and poor in 4 cases (4/60, 6.7%). There were significant differences in different fracture type groups (P = 0.013*), operation age groups (P = 0.025*) and open/closed reduction groups (P = 0.042*). There was no significant difference in K-wire fixation type groups (P > 0.05). Conclusions Patients with open reduction, the more serious fracture type, the older at the operation, were more likely to have poor AGS result. Different K-wire fixation types for CDPNF in children had the same satisfactory results.